The eye of singularity: toward an ethics of encounter in Halid Ziya’s novel Kırık Hayatlar - Ergun, Duygu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
This study is centered upon Halid Ziya’s Kırık Hayatlar, serialized in 1901 in the newspaper Servet-i Fünun; more specifically; it explores how its narration of gaze determines/shapes the ethical stance of the novel. In line with the themes that dominate the nineteenth-century medical discourse, it calls into question the very existence of truth, and examines the possibility of “knowing the other” through an appraisal of the glances the characters cast at one another upon their encounters. The gaze of the protagonists, namely Ömer Behiç and Vedide, not only reveals how to get to know and evaluate their surroundings, but also exposes the limited nature of their knowledge. The inability to know about the demeanors and experiences of other characters makes the episteme posited in Ömer Behiç’s and Vedide’s perspective limited and personal as well, for their gaze becomes constituted as a subjective experience. The narrator’s depiction of the singular gazes of the characters; therefore, invalidates their judgments towards one another. Through a linguistic and narrative construction of gaze, the novel conveys the impossibility of understanding the other; in turn, this overrules the idea of an absolute truth and a humanist morale in the novel. Consequently, the constant urge and inability to know along with encountering the absence of truth designate the tragic mode of the narrative.
Keywords: Turkish literature -- 20th century -- History and criticism.